JUNIOR HIGH SCHOOL STUDENTS' ABILITY TO COMPLETE MATHEMATICAL HOTS QUESTIONS - Samsul Hadi; Suratman Wijaya (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
ABSTRACT Mathematical High Order Thinking Skill (HOTS) problem solving is part of students' abilities which require creativity, criticality, and student analysis in solving both simple and complex problems. This study aims to analyze the ability of junior high school students in solving mathematics HOTS problems. This research uses a case study-based qualitative approach. Research participants consisted of 30 students consisting of 13 male students and 17 female students in class VIII at one of the public junior high schools in East Lombok, NTB, in the odd semester of the 2020-2021 academic year. The research sample was determined by purposive sampling. The instrument used was a description test of HOTS questions and interviews. The results showed that the ability of junior high school students in solving HOTS questions was still low both in understanding problems, making problem representations, developing strategies, and executing strategies.